2011
DOI: 10.1503/jpn.100133
|View full text |Cite
|
Sign up to set email alerts
|

Myoclonus as an indicator of infection in patients with schizophrenia treated with clozapine

Abstract: The information in this column is not intended as a definitive treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 7 publications
0
13
1
Order By: Relevance
“…7 Although rarely reported, clozapine is also known to be associated with the development of negative myoclonus, 6,8 which likely emerges in a dosedependent manner. [14][15][16] It is particularly interesting that 3 case reports described the emergence of myoclonus including negative myoclonus in patients treated with clozapine when developing respiratory tract infections. 6 In conclusion, during treatment with clozapine, clinicians must be aware of the potential for increase in the clozapine level when patients are affected by a range of infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Although rarely reported, clozapine is also known to be associated with the development of negative myoclonus, 6,8 which likely emerges in a dosedependent manner. [14][15][16] It is particularly interesting that 3 case reports described the emergence of myoclonus including negative myoclonus in patients treated with clozapine when developing respiratory tract infections. 6 In conclusion, during treatment with clozapine, clinicians must be aware of the potential for increase in the clozapine level when patients are affected by a range of infections.…”
Section: Discussionmentioning
confidence: 99%
“…,14,15 Kwak et al6 and Liang and Hsieh 15 claimed that a respiratory tract infection might influence drug metabolization via CYP enzyme suppression and thereby triggered adverse effects. de Leon and Diaz 14 examined clozapine's exact plasma concentration level and found that a severe respiratory…”
mentioning
confidence: 99%
“…Ten studies were reviews/meta-analyses [ 1 , 13 , 18 , 27 , 41 46 ], while other studies included 12 case reports [ 47 58 ]and one letter to the editor[ 15 ]. Most of the literature concerned patients aged 65 and older [ 1 , 4 , 6 , 8 10 , 12 , 18 , 35 , 38 , 41 , 45 , 47 , 49 , 51 ] while others investigated an adult population with bipolar/schizophrenic disorders [ 26 , 36 , 37 , 40 , 48 , 50 , 55 , 56 , 59 ]. No randomized clinical trials (RCTs) were identified, but one meta-analysis of 6 RTCs was found [ 27 ]( S2 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Myoclonus is a known adverse effect of clozapine that may occur with usual dosing or be an indication of infection. 7 Sialorrhea, which occurs often during the usual course of clozapine treatment, may be also explained by acute toxicity and occurred in cases 1 and 2 above. 10 Extensive workup was conducted in all 3 cases to rule out other causes of mental status changes.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that clozapine toxicity may occur in the setting of an acute infectious and/or inflammatory process as a result of reduced 1A2 activity (Table 1). [2][3][4][5][6][7][8][9] Prior cases describing clozapine toxicity as a result of infectious and/or inflammatory processes have mostly involved respiratory infections; however, involvement of gastrointestinal and urinary infections have also been described. Symptoms of toxicity in the reported cases have been generally mild to moderate and included sedation, dizziness, and confusion.…”
Section: Introductionmentioning
confidence: 99%